Total burden of cerebral small vessel disease predict subjective cognitive decline in patients with Parkinson’s disease - Qiu, Wenchao; Hu, Weili; Ge, Yingchao; Liu, Peiting; Zhao, Minghui; Lu, Haifeng; Tao, Jian; Xue, Shouru (Frontiers in Aging Neuroscience, 2024)
IntroductionThis study investigates the correlation between the total burden of Cerebral Small Vessel Disease (CSVD) and Subjective Cognitive Decline (SCD) in patients with Parkinson’s disease (PD).MethodsA cross-sectional design was employed, involving 422 patients with PD. Demographic and clinical data were collected. Brain magnetic resonance imaging (MRI) was conducted to identify CSVD markers. SCD was assessed using the Cognitive Complaints Inventory (CCI).ResultsLogistic regression analyses revealed that the total burden of CSVD and specific imaging markers, including Deep White Matter Hyperintensities (DWMH), Periventricular Hyperintensities (PVH), and Enlarged Perivascular Spaces (EPVS), were significant predictors of SCD. The total burden of CSVD demonstrated the highest predictive accuracy for SCD in PD patients.DiscussionThe findings suggest that the total burden of CSVD, as measured by MRI, could serve as a potential biomarker for early identification of cognitive decline in PD, highlighting the importance of considering vascular factors in the early detection of cognitive changes in PD.